EFFECTIVENESS OF ECONOMIC ASSESSMENT OF THE QUALITY OF HIGHER EDUCATION - Badiev Baxtinur Baxodir o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In the article, studies revealing the essence of higher education quality are divided into groups and modern approaches are summarized. An author’s approach to the socio-economic interpretation of the quality of higher education has been developed. Levels of economic development are determined based on the quality of higher education. A scientific conclusion and practical recommendations aimed at ensuring the quality of higher education and implementing comprehensive measures have been developed.